Effects of telehealth‐mediated behavioral assessments and interventions on client outcomes: A quality review. Issue 2 (23rd February 2021) - Neely, Leslie; MacNaul, Hannah; Gregori, Emily; Cantrell, Katherine
Abstract : The purpose of this review was to evaluate the quality of research focused on the effects of telehealth‐mediated behavior‐analytic assessments and interventions on client outcomes. The majority of studies utilized a single‐case methodology ( n = 44; 81%), while 10 studies (19%) used a group design. Of the 246 single‐case designs, 99 (40%) met design standards with or without reservation. For the 10 group design studies, 7 (70%) met the design standards. When evaluating the evidence offered according to the prime independent variable (e.g., behavior assessment, intervention designed for behavior reduction, and intervention designed to establish or strengthen behavior), the literature supports the use of telehealth to conduct behavior assessments and provide interventions designed to establish or strengthen behavior. Additional research is necessary to establish the use of telehealth to conduct interventions designed for behavior reduction. Implications for future research and practice are discussed.